Non-invasive actionable biomarkers for metastatic prostate cancer - Jun Luo (Asian Journal of Urology)
In the current clinical setting, many disease management options are available for men diagnosed with prostate cancer. For metastatic prostate cancer, first-line therapies almost always involve agents designed to inhibit androgen receptor (AR) signaling. Castration-resistant prostate cancers (CRPCs) that arise following first-line androgen deprivation therapies (ADT) may continue to respond to additional lines of AR-targeting therapies (abiraterone and enzalutamide), chemotherapies (docetaxel and cabazitaxel), bone-targeting Radium-223 therapy, and immunotherapy sipuleucel-T. The rapidly expanding therapies for CRPC is expected to transform this lethal disease into one that can be managed for prolonged period of time. In the past 3 years, a number of promising biomarkers that may help to guide treatment decisions have been proposed and evaluated, including androgen receptor splice variant-7 (AR-V7), a truncated AR lacking the ligand-binding domain (LBD) and mediate constitutively-active AR signaling. Putative treatment selection markers such as AR-V7 may further improve survival benefit of existing therapies and help to accelerate development of new agents for metastatic prostate cancer. In the metastatic setting, it is important to consider compatibility between the putative biomarker with non-invasive sampling. In this review, biomarkers relevant to the setting of metastatic prostate cancer are discussed with respect to a number of key attributes critical for clinical development of non-invasive, actionable markers. It is envisioned that biomarkers for metastatic prostate cancer will continue to be discovered, developed, and refined to meet the unmet needs in both standard-of-care and clinical trial settings. Keywords: Prostate cancer, Androgen receptor, AR-V7, Biomarker, CRPC